Efficacy of antiprostaglandin therapy in vernal conjunctivitis. Issue 7 (July 1987) - Meyer, E; Kraus, E; Zonis, S
Abstract : Twenty-seven patients with vernal conjunctivitis who remained symptomatic following treatment with corticosteroid drops and/or Opticrom drops (sodium cromoglycate 2%, benzalkonium chloride 0.01%) were treated with aspirin. Aspirin produced marked improvement in all patients apart from three. The possible mechanism of the efficacy of aspirin in vernal conjunctivitis is discussed.